Impacts of heat stress conditions on mortality from respiratory and cardiovascular diseases in Brazil - Oliveira, Beatriz Fátima Alves de; Jacobson, Ludmilla da Silva Viana; Perez, Letícia Palazzi; Silveira, Ismael Henrique da; Junger, Washington Leite; Hacon, Sandra de Souza (Sustainability in Debate, 2020)
This study assesses the risk of exposure to heat stress conditions and their potential impact on mortality from cardiovascular and respiratory diseases in Brazilian capital cities for warming levels of 1.5 °C, 2.0 °C and 4.0 °C in the RCP8.5 scenario. The risk of exposure and the impact of heat stress conditions on mortality were measured by the Wet Bulb Globe Temperature (WBGT) index. The impact on health was estimated by applying exposure-response curves between WBGT and health outcomes in the projections. The potential impact on mortality was measured by attributable fraction of mortality due to heat stress. The results showed an increase in heat stress conditions for Brazil, especially in the Northern and Center-Western regions. The estimated curves showed an association between the WBGT and mortality by cardiovascular and respiratory diseases in Brazil, with an upward impact trend, according to the levels of warming and heterogeneous results among the capitals. Â 